Adamantane dication fragmentation dynamics following ion collisions. Issue 15 (January 2020) - Nicolafrancesco, C; Indrajith, S; Maclot, S; Domaracka, A; Huber, B; Díaz-Tendero, S; Rousseau, P
Synopsis: Being an important exponent of diamondoids molecular class, and abundantly found in the interstellar medium, getting a better insight on its behaviour when exposed to energetic particles is of great interest. In order to do that, we performed gas phase ion-collisions to study the fragmentation dynamics of adamantane analysing the charged molecular fragments by a multicoincident mass spectrometer. With the complementary approach of quantum chemistry calculations, we obtained a better understanding on adamantane fragmentation dynamics.